RARβ gene methylation in primary glioblastomas - Atli, E. I.; Kalkan, R.; Artan, S. (WILEY-BLACKWELL, 2014)
FEBS EMBO 2014 Conference, Paris, FRANCE, AUG 30-SEP 04, 2014
Keywords: glioblastoma; methylation; RAR beta